At home in Vienna-Zu Hause in Wien Studies of exemplary affordable housing-Eine Studie und Sammlung geförderter Wiener Wohnbauten - Jadric, Mladen; Alic, Dijana (Publication Series of the Faculty for Architecture and Planning) Faculty for Architecture and Planning, 2019)
Housing, and access to affordable housing, is key to creating a just, inclusive and sustainable city. For both future and current city-shapers there is much to learn from Vienna. The Viennese have long demonstrated how to deliver high-quality, innovative and sustainable affordable housing, resulting in the creation of one of the world's most liveable and equitable cities. A product of an interdisciplinary and international joint course between TU Wien and UNSW Sydney, this book presents a collection of portraits of Viennese affordable housing projects. Each portrait offers insights into the design outcomes of each project, making this book an excellent introduction to better understand housing in Vienna.